On the weak uniform rotundity of Banach spaces - Wen D. Chang; Ping Chang (International Journal of Mathematics and Mathematical Sciences)
We prove that if Xi,i=1,2,…, are Banach spaces that are weak* uniformly rotund, then their lp product space (p>1) is weak* uniformly rotund, and for any weak or weak* uniformly rotund Banach space, its quotient space is also weak or weak* uniformly rotund, respectively.